(untitled) (Communication & Society, 2024)
Immersive journalism is a recent field of research focusing on digital technologies such as augmented reality (AR), 360° video, and virtual reality (VR). This research analyzed 69 academic articles published in the Web of Science from January 1, 2010, to December 31, 2021, using a systematic review of scientific literature (SLR). The prevalence of media effects and quantitative methodologies in investigating immersive journalism was demonstrated. The corpus analysis shows the recurrence of some key macro-concepts. We propose grouping these macro-concepts into affordances (presence, embodiment, and interactivity) and gratifications (comprehension, credibility, emotional engagement, and empathy), which affect in different extents the cognition, affectivity, and behavior of the users. This review highlights the need to expand and combine different theories and methodologies. Another important recommendation is to create specific frameworks for analyzing immersive news stories and examining their various narrative and aesthetic characteristics during both production and post-production. This article discusses the ethical and normative concerns of journalism in relation to current and future research in VR.